Haemangiopericytoma of the Larynx: A Rare Clinical Entity (Bangladesh Journal of Otorhinolaryngology, 2015)
Haemangiopericytomas are rare vascular neoplasms of the head and neck.Laryngeal involvement is even extremely rare ,with only 11 previously reported cases in the literature .We present an unusual case of a 45 years old man with obstructing left glottic mass .Tracheostomy was done for the stridor and FOL showed huge reddish vascular mass which was attached along the whole length of the undersurface of the left vocal cord.Microlaryngoscopic excisionof the whole mass was done ,with biopsy consistent with a haemangiopericytoma.Following operation tracheostomy tube was put off and he got his voice back.The patient is currently 2 years post op follow-up with no recurrence. Otolaryngologists need to be aware of this rare tumour that can be treated successfully with surgical resection.Close long term follow up is needed since recurrence can present many years after initial treatment.Bangladesh J Otorhinolaryngol; April 2015; 21(1): 47-50